A novel CeO2/Bi2WO6 composite with highly enhanced photocatalytic activity - Issarapanacheewin S. (Elsevier, 2015)
© 2015 Elsevier B.V.All rights reserved. A straight forward strategy was designed for the preparation of novel CeO2/Bi2WO6 composite photocatalysts with differing CeO2/Bi2WO6 mole ratios by hydrothermal method. The X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-vis diffuse reflectance spectrophotometry (UV-vis DRS) techniques were found to be most suitable for describing the physicochemical properties of CeO2/Bi2WO6 onto the photocatalytic activity. Photocatalytic activities of all samples were evaluated by the degradation of rhodamine B under simulated solar light irradiation. The 0.4CeO2/0.6Bi2WO6 composite exhibits highest photocatalytic activity due to the introduction of CeO2 and Bi2WO6, which can improve the separation of the electron-hole pairs.